A Comparison of Monitors and Message Passing - Staunstrup, Jørgen (DAIMI Report Series, 1978)
One of the issues which receives much attention in the field of concurrent programming is communication and synchronization primitives. Many primitives have been proposed but two main philosophies have evolved: monitors and message passing. The two programming languages Concurrent Pascal and Platon represent these two different approaches. By looking at a few algorithms written in the two languages, the two approaches are analyzed and compared.